FALSE POSITIVE DIAGNOSIS OF MYOCARDIAL INFARCTION IN EARLY REPOLARIZATION SYNDROME - V. A. Badtieva; A. S. Sharykin; V. I. Pavlov; A. V. Pachina (Кардиоваскулярная терапия и профилактика, 2017)
Early repolarization syndrome is common as ECG finding in sportsmen, and is usually due to vagotony, being usual in sportsmen. Sometimes the early repolarization might mimic pathological signs, e.g. acute myocardial infarction, that is a challenge for differential diagnostics, leading to false diagnostical decisions.